2013
DOI: 10.1103/physreve.88.010502
|View full text |Cite
|
Sign up to set email alerts
|

Dual translocation pathways in smectic liquid crystals facilitated by molecular flexibility

Abstract: We investigate translocation mechanisms in smectic A liquid crystals (LCs) by a realistic, coarse-grained model of a LC compound comprising a stiff azobenzene core with flexible tails. We observe that the molecules can permeate from one smectic layer to the next via two different mechanisms, with and without significant reorientation, the former being facilitated through transverse interlayer intermediates. This is possible due to the intrinsic flexibility of the molecules. The two processes lead to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Experimental and numerical studies of lyotropic smectics formed by long rigid rods (such as filamentous fd virus) demonstrated a hopping transport 120,121 : the rods jump from one layer to another without significant reorientation. However, when the smectic is formed by flexible molecules, the layer-to-layer translocation can also happen through an intermediate state, in which the molecules find themselves between the layers in a reoriented state 122 .…”
Section: Static Distortionsmentioning
confidence: 99%
“…Experimental and numerical studies of lyotropic smectics formed by long rigid rods (such as filamentous fd virus) demonstrated a hopping transport 120,121 : the rods jump from one layer to another without significant reorientation. However, when the smectic is formed by flexible molecules, the layer-to-layer translocation can also happen through an intermediate state, in which the molecules find themselves between the layers in a reoriented state 122 .…”
Section: Static Distortionsmentioning
confidence: 99%
“…ref. [58] This result is somewhat surprising as the molecular flexibility is believed to play an important favorable role in interlayer diffusion, [59] and hard spherocylinders with low aspect ratio show the opposite behavior with respect to P5. From the results in Figure 11, the three high-temperature phases are clearly fluid with translational diffusion coefficients of the order of 10 À9 m 2 s À1 , which is comparable with those of other nematics [57] and of sexithiophene in the same high-temperature range.…”
Section: Dynamicsmentioning
confidence: 99%
“…At the same time, this CG model shows remarkable state point transferability and reproduces the LC-isotropic phase transition upon heating and cooling [39]. Such a CG LC model-since it is on the one hand sufficiently coarse grained to study a variety of processes in the LC phase while being at the same time still very closely related to an underlying chemically realistic atomistic description, e.g., allowing for realistic molecular flexibility-is able to give new insights into for example microscopic dynamics in LC phases [40] Figure 1. A transferable coarse-grained (CG) model for a liquid crystalline molecule that reproduces the ordered/disordered phase transition while at the same time being highly consistent with an atomistic level of resolution.…”
Section: Transferability Of Coarse-grained Modelsmentioning
confidence: 99%
“…This is achieved by the choice of reference state point, namely the supercooled liquid just below the smectic-isotropic phase transition which is characterized by a high degree of local nematic order while being overall isotropic, for details see Reference [39]. Left panel: snapshot of a CG simulation in the LC state with a backmapped atomistic structure superimposed; Right panel: This model allows mechanistic studies of dynamic processes in smectic systems, where the influence of the intrinsic flexibility of the molecules on the free energy of different permeation pathways can be elucidated (reprinted from [40]). …”
Section: Transferability Of Coarse-grained Modelsmentioning
confidence: 99%
See 1 more Smart Citation